PENGARUH PEMANFAATAN BIG DATA ANALYTICS ATAS INTEGRASI NIK-NPWP TERHADAP TINGKAT KEPATUHAN PAJAK - Fathurahman, Iman Mastur; Murtanto; Nugroho, Eko Adi (Jurnal Akuntansi Trisakti, 2025)
This study explores the effect of the integration of the Population Identification Number (NIK) into the Taxpayer Identification Number (NPWP) supported by Big Data Analytics technology on the level of tax compliance in Indonesia. In the digital era, the integration of NIK-NPWP is a strategic policy that aims to simplify tax administration, expand the taxpayer database, and reduce tax avoidance. However, the level of taxpayer compliance remains a significant challenge. Using exploratory methods and thematic analysis of qualitative data, this study examines the effectiveness of Big Data Analytics in detecting tax violations and understanding taxpayer perceptions of this policy. Attribution theory is used to analyze compliance motivation, both intrinsic and extrinsic. The results of the study show that the integration of NIK with NPWP on the use of Big Data Analytics to improve tax payment compliance. This is consistently felt by both the Fiscus and taxpayers. The results of this study can be input for the government in formulating more effective policies in improving tax compliance. The results of this study can be input for the government in formulating more effective policies in improving tax compliance. In addition, this study can also contribute to the taxation study, especially related to the use of information technology in improving the efficiency and effectiveness of the taxation system.